2013
DOI: 10.11604/pamj.2013.15.95.2173
|View full text |Cite
|
Sign up to set email alerts
|

Mental distress among university students in Ethiopia: a cross sectional survey

Abstract: IntroductionMental distress is becoming a common health problem among university students. There is limited information in this regard in Ethiopia. This study was aimed to determine the prevalence and associated factors of mental distress among students in Adama University.MethodsA cross-sectional study was conducted in March2011. Four hundred and thirteen students were participated in the study. Simple random sampling technique was applied to select the study participants. Self-Reporting Questionnaire-20(SRQ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
94
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(135 citation statements)
references
References 24 publications
(17 reference statements)
24
94
10
Order By: Relevance
“…Similarly, a study conducted in United State College showed that, 32% of university students have reported to have symptoms of mental health problems [16]. Another study reported that the prevalence of mental health distress is (21.6%) among Adama university undergraduate regular students [17].…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, a study conducted in United State College showed that, 32% of university students have reported to have symptoms of mental health problems [16]. Another study reported that the prevalence of mental health distress is (21.6%) among Adama university undergraduate regular students [17].…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, our finding is lower than findings stated by Alsanosy RM et al, in higher education institution of Jazan region (24.8%) [5], study from Saudi Arabia secondary high schools mentioned by Mahfouz MS et al (24.2%) [24], South Western Uganda reported by Ihunwo and Amadi (32%) [25], from Addis Ababa private and Butajira governmental schools (35.6% and 31%), respectively as mentioned by Kassaye M et al [15], staff of Jimma University (46%) [26], Jimma city community (37.8%) [9], Jimma university students (33.1%) [16], Hosanna Health science students (27.7%) [17], southwestern Ethiopia (64.9%) [18], Arbaminch town (27%) [27], Adama University (40%) [10], Axum University students (28.8%) [19], and in four colleges of North western Ethiopia (26.7%) [28]. The possible reason might be due to their current accommodation that almost all of the students in this study area are using bed and food services in the university.…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that khat chewing, smoking and alcohol intake have a significant negative influence on academic achievements of university students [16]. All in all, different prevalence were reported form different parts of Ethiopia; for instance; 27.7% from Hosanna Health Science College students in 2010 [17]; 64.9% from South-Western Ethiopia [18]; 40% from Adama University [10]; 28% from Axum University [19] and 22.3% from North-Western Ethiopia [20]. Moreover, study conducted among 754 College students in Bahir Dar town showed that the overall prevalence of khat was 19.6% [21].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations